ANALYSIS OF THE HEAD OF NAVAL ACCOUNTING PROSPECTIVE ASSESSMENT SYSTEM OF THE INDONESIAN NAVY BASED ON COMPETENCE BY ANALYTIC NETWORK PROCESS (ANP) - Joko Purnomo; Sukmo Hadi Nugroho; Adi Bandono; Edy Widodo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
In the Navy's Posture Draft at 2005 to 2024, the readiness of Navy organization is determined by the component of Indonesian Navy's force consisting of personel, Alat Utama Sistem Persenjataan (defense system) and the method system it self. The Navy's Financial Accounting Unit as a Level IV Financial Agency is a unit that’s asked to assist the Commander / Head of the Unit to managing the management and administration of state finances. The selection or participation process is not only based on job descriptions, but must involve gentle and difficult factors. This study focuses on system analysis with several criteria in the position selection of Head of the accounting unit including soft and hard competencies and using the ANP method. This study aims to develop models and relevant criteria for selection of candidates for the Head of the Accounting Unit and provide alternative selection methods that can help the methods that have been used previously to get potential buyers who able to perform special tasks of the Navy. Furthermore, to process data, a literature study was conducted on the concept of MCDM, the Analytic Network Process (ANP). The Head of Account prospective scoring system application using Hypertext Preprocessor (PHP). The results of the study, obtained 5 criteria in the acquisition of Prospective Head of Accounts, these are Education, Competence, Health, Physical condition and performance. Then it produced a Candidate Account system in the form of software. Keyword : head of the accountant unit, soft and hard competencies, analytic network process (ANP),hypertext preprocessor (PHP)